Kinematics analysis of freestyle swimming athletes at the 2019 Indonesia Open Aquatic Championship (IOAC) - Emir Rizkanto, Billy; Rusdiawan, Afif (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
This study aims to determine the kinematics of the men's 50 and 100 meter freestyle swimming athletes. Research method uses quantitative descriptive with 50 meter swimmers and 100 meter freestyle men at the 2019 IOAC championship. Instrument used was a Sony Rx-10Mark IV camera placed in the highest stands at a distance of 25 m in a 50-meter pool. Video results analyzed using the Kinovea 0.8.27 software by calculating the SF,SV,SR, and SL. The results showed that the average number of a 50meter had an SF of 13.06,SV of 1.89 m.s-1,SR of 59.08 cycles.min-1, and SL of 1.92 m.cycle-1. The 100 meter number, the average SF value is 11.8 at a distance of 50-meter and 12.08 at 100 meter. In comparison, the SV average is 1.73 m.s-1 at a distance of 50 and 1.72 m.s-1 at a distance of 100-meter. SR the average is 46.35 cycles.min-1 distance of 50 meter and 50, 2 100 m distance. SL the average is 2.25 m.cycle-1 distance of 50-meter and 2.08 distance of 100-meter. Conclusion, are differences in kinematics of swimming between the men's 50 meter and 100 meter freestyle in SV and SR,while those in SF and SL tend to be the same.